On the Dynamics of a Big Drop in Acoustic Levitation - Gaete-Garreton, L; Vargas-Hernandez, y; Meneses-Díaz, J; Cancino-Jaque, E (Elsevier B.V., 2023)
The acoustic levitation of a drop is a complex process that needs a high-intensity non-linear acoustic field; the sound pressure level has to be sufficient to raise the drop but not too large to avoid its atomization, limiting the maximum size of a levitated drop. In this paper, we present an experimental study of big drops levitation with a volume up to 166±2μl and with an effective diameter 6.82±0.03mm, figures one magnitude order larger than the maximum drop volume reported in the literature. Our acoustic levitator produces an acoustic field with a different shape than the field produced by a typical levitator. Our measurements and simulations of the acoustic field and drop dynamics suggest that the levitation of big drops is possible because the distribution of radiation pressure over the drop surface in our system differs from that in a typical acoustic levitator; its maximum value appears on the top surface of the drop and not in its equator. In addition, we determined the upper and lower limits of sound pressure necessary for the levitation of drops of various sizes that allow our system. © 2023 The Authors
Keywords: Acoustic levitation; Single drop; Non -linear acoustic